2021
DOI: 10.3390/su132313145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Experimental Warming and Canada Goldenrod Invasion on the Diversity and Function of the Soil Nematode Community

Abstract: Both global warming and alien plant invasion can affect the biotic communities in the soil. Most studies are focused on the soil microbial community, but little is known about how global warming, along with alien plant invasion, affects the diversity and function of the soil nematode community. In this study, the individual and interactive effects of experimental warming and Canada goldenrod (Solidago canadensis L.) invasion on soil nematode communities were measured. Experimental air warming, in combination w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…During vegetation community alterations (such as succession or degradation), the substrate (i.e., litter, residues, and root exudates) input into the soil from the plant may be an essential mechanism to regulate soil available nutrients. Therefore, adding mulch to the soil increases the water and nutrient retention capacity, which deliberately enhances soil carbon capacity, composition, and fertility to increase the production of crops [43][44][45][46]. Previous studies have demonstrated that the activity of microbial extracellular enzymes could be inhibited through interactions with substrates released by Spartamina alterniflora [44].…”
Section: Effects Of Vegetation Community Alteration On the Activities...mentioning
confidence: 99%
“…During vegetation community alterations (such as succession or degradation), the substrate (i.e., litter, residues, and root exudates) input into the soil from the plant may be an essential mechanism to regulate soil available nutrients. Therefore, adding mulch to the soil increases the water and nutrient retention capacity, which deliberately enhances soil carbon capacity, composition, and fertility to increase the production of crops [43][44][45][46]. Previous studies have demonstrated that the activity of microbial extracellular enzymes could be inhibited through interactions with substrates released by Spartamina alterniflora [44].…”
Section: Effects Of Vegetation Community Alteration On the Activities...mentioning
confidence: 99%
“…In 2004, S. canadensis , together with 17 other plant species was recorded as an invasive weed in Lithuania [ 10 ]. Canadian goldenrod is considered to be one of the greatest threats to biodiversity and native species communities increasing the negative impact on natural ecosystems along with factors such as habitat degradation, change in landscape, pollution, exploitation and climate change [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%